Comparative efficacy of eoil and foliar application of zinc on Garlic (Allium sativum L.) production in sandy loam soils of Rajasthan - Ronak Kuri; Santosh Choudhary; S K Moond; P. R. Raiger; Suman Pooniya (Current Horticulture, 2025)
An experiment was conducted to assess the impact of various levels and modes of zinc (Zn) application on garlic (Allium sativum L.) at College of Agriculture, Jodhpur during rabi 2021-22. There were seven treatments, three soil applications of ZnSO4 (5, 10, and 15 kg/ha), three foliar applications (FA) of ZnSO4 (0.3%, 0.5%, and 0.7%), and a control in randomized block design with three replications. Results indicated that ZnSO4 applications significantly improved growth parameters, with the highest plant height and number of leaves observed with ZnSO4 15 kg (SA) and ZnSO4 0.7% (FA). ZnSO4 0.7% (FA) also recorded significantly highest values of bulb weight, neck thickness, and weight of 50 cloves. Both ZnSO4 15 kg (SA) and ZnSO4 0.7% (FA) treatments achieved the maximum bulb yield of 15.4 t/ha, compared to the control (11.5 t/ha), indicating a 33.9% increase in bulb yield. Zinc Use Efficiency was highest for ZnSO4 15 kg (SA) at 0.29 t/ha/kg ZnSO4. Economic analysis revealed the highest net returns (Rs. 465,154/ha) for ZnSO4 0.7% (FA) and the highest B:C ratio (3.08) for ZnSO4 15 kg (SA). These results highlights the higher efficacy of ZnSO4 applications, particularly with foliar, enhancing growth, yield, quality, and economic returns of garlic in arid regions.